ANALISIS KECELAKAAN PARAH PADA PRESSURIZED WATER REACTOR DENGAN BACKWARDS METHOD - Udiyani, Pande Made; Kuntjoro, Sri; Pane, Jupiter Sitorus (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Anticipation of NPP severe accident becomes very important in nuclear technology after a severe accident at Japan's Fukushima nuclear reactor. Based on these problems then do research on the analysis of the consequences of severe accidents PWR (Pressurized Water Reactor) to learn from the Fukushima reactor accident management with a new method known as the backwards method. Backwards method is based on the results of measurements of radiation exposure received by the public, to estimate of core damage in NPP reactors. Analysis of the consequences of PWR severe accidents with bakwards method has been carried out to potential candidates site in Indonesia as Semenajung Muria, Serang Coastal, site with single weather stability such as C, D, E, and F Stability. The results of the backwards method calculation can be used to determine the severity of the accident and the verification of a particular reactor with a capacity of 1000 MWe PWR to site in Indonesia.